Evolutionary adaptations of cyanobacterial polyhydroxybutyrate (PHB) biosynthesis and metabolic pathways in Spirulina, Arthrospira, and Limnospira spp - Fayaazuddin Thajuddin; Asraf Sithikka Rasheed; Prakash Palanivel; Shakena Fathima Thajuddin; Thajuddin Nooruddin; Dhanasekaran Dharumadurai (Scientific Reports)
Abstract Cyanobacteria are photosynthetic microorganisms with significant biotechnological potential owing to their ability to produce valuable biopolymers such as polyhydroxybutyrate (PHB). This study focuses on PHB production in the cyanobacteria, Limnospira fusiformis NRMCF6962 and Spirulina major NRMCF6963, under nitrogen-limited conditions. Qualitative and quantitative analyses confirmed PHB accumulation in L. fusiformis and its absence in S. major. Whole-genome sequencing of L. fusiformis revealed 5,177 coding sequences. Comparative genomic analysis of 26 cyanobacterial strains belonging to genera of Spirulina, Arthrospira, and Limnospira revealed significant variations in gene content, particularly within PHB biosynthesis pathways. Functional annotation revealed that PHB metabolism is absent in S. major, which instead relies on alternative stress-response pathways including chlorophyll degradation, selenocysteine metabolism and xanthine metabolism. Phylogenomic and metabolic pathway analyses suggests an evolutionary adaptation among the three genera of Oscillatoriales, with S. major as a divergent species from PHB-producing descendants. Orthologous Average Nucleotide Identity and digital DNA-DNA hybridization validated the taxonomic distinction between two major clades within strains. Metabolic insights revealed the critical role of PHB and alternative metabolic pathways in cyanobacteria for stress adaptation. This research advances the understanding of PHB metabolism and evolutionary mechanisms in cyanobacteria, underscoring the potential for cyanobacterial strain improvement and scale-up in bioprocess industry.